DETERMINATION OF POVERTY LEVELS IN ACEH PROVINCE - Uswah, Uswatun Hasanah; safrina, lia (I-Finance Journal, 2024)
This research was conducted to analyze the effect of the Open Unemployment Rate, Inflation Rate, HDI Level and ZIS Realization on the Poverty Level in Aceh Province. The data secondary from data Aceh Central Statistics Agency (BPS) in the form of data on the Percentage of Poor Population as the dependent variable, data from 18 districts and 5 cities in Aceh Province represented by data on the Open Unemployment Rate, Inflation Rate, HDI Rate and data on the realization of Zakat, Infaq and Sadaqah (ZIS) from Baitul Mal Aceh in 2007-2021. The data analysis technique used to test the hypothesis in this study is multiple linear regression analysis. The results of this study indicate that; Partially the unemployment variable has no significant effect on the poverty rate in Aceh Province, this can be seen from the sig value which is 0.107 > 0.05. The inflation that has no significant effect on the poverty, this can be seen from sig value wich is 0.309>0.05.  The human development index variable that also has no significant effect on the poverty, its a sig value of 0.162 > 0.05. The ZIS realization variable that has significant effect on the poverty this can be seen from the sig value which is 0.000 < 0.05.. Based on the description above, it can be concluded that open unemployment, the inflation rate and the HDI level have no effect on poverty and the only the realization of zakat has an effect on the poverty level in Aceh province.